Enantioselective addition of diethylzinc to aldehydes catalyzed by aziridine carbinols. Issue 15 (31st August 2015) - Wang, Xiaojuan; Zhao, Wenxian; Li, Gaowei; Liu, Guanjun; Wang, Jin; Wang, Mincan; Liu, Lantao
Graphical abstract: Abstract: A series of enantiopure aziridine carbinols were synthesized from commercially available starting materials (l -serine and piperonylaldehyde), and characterized by 1 H NMR, 13 C NMR, HRMS, and IR. Their enantioselective induction behaviors were evaluated as chiral ligands in the asymmetric addition of diethylzinc and phenylethynylzinc to aryl and α, β-unsaturated aldehydes. Chiral aziridine carbinol1h was found to catalyze the asymmetric addition of diethylzinc to aldehydes at low catalyst loadings (as little as 1 mol %), and the conversion rates were close to quantitative (up to 97% yield) with good to excellent enantiomeric excesses (up to 98% ee). A possible catalytic reaction mechanism is proposed. Abstract : (2 S )-1-Piperonylmethylaziridin-2-yl(dimethyl)methanol: C13 H17 NO3 [ α ]D 20 = +4.5 ( c 0.594, CHCl3 ) Source of chirality:l -Serine Absolute configuration: ( S ) Abstract : (2 S )-1-Piperonylmethylaziridin-2-yl(di- n -propyl)methanol: C17 H25 NO3 [ α ]D 20 = −12.7 ( c 1.05, CH2 Cl2 ) Source of chirality:l -Serine Absolute configuration: ( S ) Abstract : (2 S )-1-Piperonylmethylaziridin-2-yl(di- i -propyl)methanol: C17 H25 NO3 [ α ]D 20 = −117.1 ( c 0.564, CHCl3 ) Source of chirality:l -Serine Absolute configuration: ( S ) Abstract : (2 S )-1-Piperonylmethylaziridin-2-yl(di- n -butyl)methanol: C19 H29 NO3 [ α ]D 20 = −20.2 ( c 1.05, CH2 Cl2 ) Source of chirality:l -Serine Absolute configuration: ( S ) Abstract : (2 S )-1-Piperonylmethylaziridin-2-yl(di- i -butyl)methanol: C19 H29 NO3 [ α ]D 20 = −61.0 ( c 1.05, CH2 Cl2 ) Source of chirality:l -Serine Absolute configuration: ( S ) Abstract : (2 S )-1-Piperonylmethylaziridin-2-yl(di-cyclopropyl)methanol: C17 H21 NO3 [ α ]D 20 = −27.2 ( c 1.05, CH2 Cl2 ) Source of chirality:l -Serine Absolute configuration: ( S ) Abstract : (2 S )-1-Piperonylmethylaziridin-2-yl(dibenzyl)methanol: C25 H25 NO3 [ α ]D 20 = −24.3 ( c 1.05, CH2 Cl2 ) Source of chirality:l -Serine Absolute configuration: ( S ) Abstract : (2 S )-1-Piperonylmethylaziridin-2-yl(diphenyl)methanol: C23 H21 NO3 [ α ]D 20 = −2.0 ( c 1.05, CH2 Cl2 ) Source of chirality:l -Serine Absolute configuration: ( S )